2016
DOI: 10.1016/j.adolescence.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Examining stress and coping as a mediator for internalizing symptomatology: A comparison between sexual minority and majority first‐year college students

Abstract: Sexual and gender minority (SGM) adolescents experience unique stressors and elevated internalizing symptoms. This study examines differences in coping styles between SGM and heterosexual adolescents and the potential mediating roles of stress and coping styles. Analyses indicated that SGM (N ¼ 75) adolescents reported higher levels of internalizing symptoms (depression, anxiety, and distress), higher use of maladaptive coping styles (denial and blame), lesser use of adaptive coping styles (reframing and relig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 44 publications
3
14
0
Order By: Relevance
“…Consistent with previous research on sexual minority youth (Marshal et al, 2013) and first-year college students (Riley et al, 2016), we found that students in the SGM group reported significantly higher rates of depression when compared to those who self-identified as heterosexual. We also found that Hispanic race was associated with and predictive of higher levels of depression.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with previous research on sexual minority youth (Marshal et al, 2013) and first-year college students (Riley et al, 2016), we found that students in the SGM group reported significantly higher rates of depression when compared to those who self-identified as heterosexual. We also found that Hispanic race was associated with and predictive of higher levels of depression.…”
Section: Discussionsupporting
confidence: 90%
“…Przedworski et al (2015) Series of regressions After controlling for demographic variables, results suggested that social stressors decreased the magnitude of the association between sexual minority status and depression 27. Riley et al (2016) Series of regressions Bootstrapping…”
Section: Physical or Sexual Violencementioning
confidence: 99%
“…Previous studies shows that anxiety, depression, and stress are more frequent among SGM students (14,82). Minority students consider the diverse educational environment as essential or as an advantage in several one-institutional surveys (22,83).…”
Section: Discrimination and Diversity In The Universitymentioning
confidence: 96%
“…Perceived stress could have a signi cant impact on the performance of students and on burnout (93)(94)(95). Some studies reported the prevalence of higher stress levels among minority students (14)(15)(16)82). Some studies raise the issue that the performance of students, professional personality, and habits related to alcohol or drug consumption are in uenced by intense stress as well (87,89,95).…”
Section: Experienced Stress and Burnoutmentioning
confidence: 99%